The Impact of Transformational Leadership and ICT Utilization on MSMEs Performance: Exploring The Mediating Role of Digital Literacy - Sunarso, Budi; Ausat, Abu Muna Almaududi; Wanof, M. Indre; Hidayat, Rahmat Al; Raharjo, Itot Bian (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: Transformational leadership is becoming increasingly relevant in the digital era, where the ability to rapidly adapt to new technologies and market changes is key to success. However, effective adoption of Information and Communication Technology (ICT) will not yield optimal impact without adequate digital literacy among MSME actors.Purpose: This study aims to explore the relationship between transformational leadership, ICT utilization, and MSME performance, with digital literacy as a mediating variable.Design/methodology/approach: This study uses a quantitative technique to investigate the correlations between pertinent variables using the SEM-PLS methodology. One hundred MSMEs in Yogyakarta, Indonesia, were the subject of the study, which used an online questionnaire to gather data.Findings/Results: The findings of this study reveal that transformational leadership and ICT utilization have a positive and significant impact on MSME performance in the culinary, creative, and tourism sectors in Yogyakarta. Digital literacy is proven to be a mediating variable that strengthens the relationship between these two factors and MSME performance.Conclusion: Transformational leadership, ICT utilization, and digital literacy significantly enhance MSME performance in Yogyakarta's culinary, creative, and tourism sectors. Transformational leadership improves productivity, product quality, profitability, and revenue growth, while ICT utilization, supported by digital literacy, strengthens MSME performance. Digital literacy acts as a key mediator, amplifying the effects of leadership and technology adoption through competencies like photo-visual, reproduction, branching, information, and socio-emotional literacy, enabling MSMEs to maximize technological and leadership benefits.Originality/value (State of the art): This study uniquely integrates digital literacy as a mediating variable between transformational leadership, ICT utilization, and MSME performance in Yogyakarta's culinary, creative, and tourism sectors. It fills a gap in existing research by examining how digital literacy enhances the impact of transformational leadership and ICT on MSME success, offering new insights for digital transformation strategies in emerging markets. Keywords: transformational leadership, ICT utilization, digital literacy, MSME performance